Economic Theory of Inflation - Emerson Abraham Jackson (ZBW - Leibniz Information Centre for Economics, 2024)
This paper explores the Economic Theory of Inflation, meticulously progressing from fundamental concepts to intricate mathematical models. Investigating causes and consequences, the study draws on pertinent economic theories and empirical evidence. Key findings elucidate the multifaceted nature of inflation, considering Demand-Pull, Cost-Push, and Phillips Curve theories. Mathematical models, including the Fisher Equation and Adaptive Expectations Model, offer quantitative insights into inflation dynamics and expectations. The paper culminates by addressing the imperative of effective economic management, advocating a judicious mix of monetary and fiscal strategies for achieving price stability and sustainable economic growth. The synthesis of economic theory, empirical analysis, and policy considerations contributes to an informed and nuanced understanding of the Economic Theory of Inflation, crucial for policymakers navigating the complexities of contemporary economies. – – Cet article explore la Théorie économique de l'inflation, progressant méticuleusement des concepts fondamentaux aux modèles mathématiques complexes. En enquêtant sur les causes et conséquences, l'étude s'appuie sur des théories économiques pertinentes et des preuves empiriques. Les principales conclusions éclairent la nature multifacette de l'inflation, en considérant les théories de la demande, des coûts et de la courbe de Phillips. Les modèles mathématiques, y compris l'Équation de Fisher et le Modèle des attentes adaptatives, offrent des aperçus quantitatifs sur la dynamique et les attentes de l'inflation. L'article se termine en abordant l'impératif d'une gestion économique efficace, préconisant un mélange judicieux de stratégies monétaires et fiscales pour atteindre la stabilité des prix et une croissance économique durable. La synthèse de la théorie économique, de l'analyse empirique et des considérations politiques contribue à une compréhension éclairée et nuancée de la Théorie économique de l'inflation, cruciale pour les décideurs naviguant dans les complexités des économies contemporaines.
Keywords: E31; E52; 330; Inflation; Economic Theory; Inflation Control